2018
DOI: 10.3390/cancers10100364
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Cancer Cells to Radiation and Topoisomerase I Inhibitor Camptothecin Using Inhibitors of PARP and Other Signaling Molecules

Abstract: Radiation and certain anticancer drugs damage DNA, resulting in apoptosis induction in cancer cells. Currently, the major limitations on the efficacy of such therapies are development of resistance and adverse side effects. Sensitization is an important strategy for increasing therapeutic efficacy while minimizing adverse effects. In this manuscript, we review possible sensitization strategies for radiation and anticancer drugs that cause DNA damage, focusing especially on modulation of damage repair pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…The molecular basis of p53-dependent apoptotic pathway in HCC cells was also analyzed by the expression of apoptosis markers, that is, cleaved caspase-3 and cleaved PARP functioned in the execution of the intrinsic mitochondrial apoptotic pathway. The proteolytic cleavage of PARP facilitated cellular disassembly and undergone apoptosis[33,34]. According to our data, with the presence of p53, overexpression of GAS2 could increase the level of cleaved caspase-3 and cleaved PARP induced by etoposide.…”
Section: Discussionmentioning
confidence: 68%
“…The molecular basis of p53-dependent apoptotic pathway in HCC cells was also analyzed by the expression of apoptosis markers, that is, cleaved caspase-3 and cleaved PARP functioned in the execution of the intrinsic mitochondrial apoptotic pathway. The proteolytic cleavage of PARP facilitated cellular disassembly and undergone apoptosis[33,34]. According to our data, with the presence of p53, overexpression of GAS2 could increase the level of cleaved caspase-3 and cleaved PARP induced by etoposide.…”
Section: Discussionmentioning
confidence: 68%
“…PARP inhibitors were originally developed to sensitize tumors to the effects of DNA damaging agents, including ionizing radiation, temozolomide, and topotecan. In fact, PARP inhibitors have successfully sensitized tumors to radiation and to camptothecin, a topoisomerase I inhibitor [62,63]. However, the combination of gemcitabine, doxorubicin, and taxan showed no significant synergies [64,65].…”
Section: Combination Effect Of Conventional Chemotherapy According Tomentioning
confidence: 99%
“…At this point, the PARP inhibitor lets the trapping of TOP1cc continue by preventing TDP1 from removing the covalent attachment of TOP1, as PARP1 recruits TDP1 through PARylation. This is due to the regulation of PARylation activity by PARP inhibitors, which has the same effect on all PARP inhibitors developed in the clinic [63,77,79]. Those applying combination therapies of PARP inhibitors and chemotherapy within the clinic should carefully consider the mechanism(s) of action prior to selecting the drug.…”
Section: Nct01924533 [32] IIImentioning
confidence: 99%
“…PARP inhibitors were initially designed to make tumors vulnerable to DNA-damaging agents such as radiation and chemotherapeutic agents. Indeed, PARP inhibitors succeeded in sensitizing tumor cells to topoisomerase 1 inhibitors (e.g., camptothecin) and radiation [141]. However, it has been reported that the combination of PARP inhibitors with doxorubicin, gemcitabine, and taxan has no significant synergistic effects [142].…”
Section: Combination Therapies Ddr Inhibitors and Dna-damaging Agentsmentioning
confidence: 99%